Rutin prevents seizures in kainic acid-treated rats: evidence of glutamate levels, inflammation and neuronal loss modulation. Issue 20 (23rd September 2022) - Chang, Anna; Chang, Yi; Wang, Su-Jane
Abstract : Pretreatment of rats with rutin attenuated KA-induced seizures and neuronal loss by decreasing glutamatergic hyperactivity and IL-1R1/TLR4-related neuroinflammatory casade. Our findings provide clues to understand the mechanism of rutin in epilepsy intervention. Abstract : Rutin, a naturally derived flavonoid molecule with known neuroprotective properties, has been demonstrated to have anticonvulsive potential, but the mechanism of this effect is still unclear. The current study aimed to investigate the probable antiseizure mechanisms of rutin in rats using the kainic acid (KA) seizure model. Rutin (50 and 100 mg kg −1 ) and carbamazepine (100 mg kg −1 ) were administered daily by oral gavage for 7 days before KA (15 mg kg −1 ) intraperitoneal (i.p.) injection. Seizure behavior, neuronal cell death, glutamate concentration, excitatory amino acid transporters (EAATs), glutamine synthetase (GS), glutaminase, α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptor subunits GluA1 and GluA2, N -methyl-D-aspartate (NMDA) receptor subunits GluN2A and GluN2B, activated astrocytes, and inflammatory and anti-inflammatory molecules in the hippocampus were evaluated. Supplementation with rutin attenuated seizure severity in KA-treated rats and reversed KA-induced neuronal loss and glutamate elevation in the hippocampus. Decreased glutaminase and GluN2B, and increased EAATs, GS, GluA1, GluA2 and GluN2A were observed with rutin administration. Rutin pretreatment also suppressed activated astrocytes, downregulated the protein levels of inflammatory molecules [interleukin-1β (IL-1β), interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α), high mobility group Box 1 (HMGB1), interleukin-1 receptor 1 (IL-1R1), and Toll-like receptor-4 (TLR-4)] and upregulated anti-inflammatory molecule interleukin-10 (IL-10) protein expression. Taken together, the results indicate that the preventive treatment of rats with rutin attenuated KA-induced seizures and neuronal loss by decreasing glutamatergic hyperactivity and suppressing the IL-1R1/TLR4-related neuroinflammatory cascade.